Fertilization, hatching, and survival rates in purebed triploid native catfish, Clarias macrocephalus x Clarias macrocephalus using cold shook treatment. - Pedrosa, Kristin Mae E.
Clarias macrocephalus is the preferred catfish species due to its delicious and tender meat. However, its culture is not so widespread because of slow growth and scarcity of seed. Induction of triploidy by cold shock treatment on newly fertilized eggs is a favorable method of obtaining sterile strains which results to better feed conversion ratio and rapid growth than the diploid fish. Newly fertilized C. macrocephalus x C. macrocephalus were exposed to 5 degrees, 7 degrees, and 9 degrees centigrade for fifteen minutes to produce triploid purebreds. Fertilization, hatching and post-hatching (day 2 and day 5) survival rates were determined. Eggs exposed to cold shock treatments showed poor performance in terms of fertilization, hatching and survival rates as compared to the untreated eggs. However, eggs exposed to 9 degrees centigrade treatment showed higher hatching (71.31 percent) and post-hatching survival rates (55.42 percent and 60.00 percent) than the other experimental treatments (5 degrees centigrade and 7 degrees centigrade). The use of 7 degrees centigrade was generally less effective in ensuring survival of triploids due to the presence of deformed fishes.